(untitled) (Journal of Engineering, 2025)
Metal foam has recently been used in many engineering applications, such as solar collectors, heat exchangers, and cooling of electronic devices, which calls for studying different cases of using metal foam in these applications. The current study conducts a numerical analysis of heat transfer and fluid flow characteristics for air in a rectangular channel filled with high-porosity copper foam. The study examined the thermal performance for two cases of gradient pore density, which are arranged as (10-20-40) PPI and (40-20-10) PPI. These cases were compared with two other cases for constant pore density, 10 and 40 PPI, and empty cases. The ANSYS FLUENT 20.0 employed the Darcy-Forchheimer extended Brickman model in the two-dimensional domain with the local thermal non-equilibrium model (LTNE) for the energy equation to obtain the numerical simulation for this study. The working parameters included air with Re from 200 to 2100 and applied heat flux from 450 to 6000 W/m2. The results indicated that employing metal foam with a low pore density led to a decrease in both the Nusselt number and pressure drop. Both gradient cases exhibited Nusselt numbers and friction factors that fell within the range of the constant PPI cases, but one of the gradient cases increased the performance factor by 10%. In general, the PPI configuration of 10-20-40 exhibited a higher heat transfer coefficient in comparison to the 40-20-10 PPI arrangement with the same pressure drop.